P–001 Effect of mild α -chymotrypsin treatment of highly viscous semen samples on fertilization rates. (6th August 2021) - Schallmoser, A; Verguts, J; Allam, J P; Sänger, N
Abstract: Study question: The main objective of this study was to examine the influence of mild α -chymotrypsin treatment of highly viscous semen samples on the fertilisation rate after artificial reproductive treatment (ART). Summary answer: The use of mild α -chymotrypsin treatment of semen samples in case of hyperviscosity does not appear to impact negatively on the fertilization rates after ART. What is known already: Highly viscous semen reduces sperm motility significantly and can contribute to infertility. When processing semen samples, few techniques exist to induce liquefaction in case of seminal hyperviscosity such as different washing steps and mechanical treatment. The use of α -chymotrypsin seems controversial due to possible negative effects on fertilisation rates after IVF. Study design, size, duration: All patients were recruited at the Department of Gynecological Endocrinology and Reproductive Medicine, University Hospital of Bonn, Germany from July first 2018 till June first 2019. Anonymized data on age, number of previous pregnancies and deliveries were retrospectively collected. The study group consisted of a cohort of 52 couples meeting the inclusion criteria of highly viscous semen and were compared to a cohort control group of 88 couples. Participants/materials, setting, methods: The fertilization rate of 52 ART cycles was examined following IVF using a low dose of α -chymotrypsin to induce liquefaction of highly viscous semen and was compared to a control group of 88 ART cycles. Data was analyzed using SPSS version 25. A Mann Whitney U test was used to compare continuous parameters between groups. Main results and the role of chance: The study group consisted of a cohort of 52 couples meeting the inclusion criteria of highly viscous semen and were compared to a cohort control group of 88 couples. The Fertilization rate between the two groups was not significant (p < 0.146, Mann-Whitney U test), with a rate of 57.95 in the study group compared to 57.53 in the control group. Our analysis showed no significant differences in male and female age, male abstinence period, semen volume, sperm concentration, total sperm count, and total progressive sperm count between the two groups. We observed a significant difference [p = 0.025] in the progressive motility and a borderline significance in the total progressive sperm count [p = 0.052] between α -chymotrypsin treated samples and the non α -chymotrypsin treated samples. Analyzing the clinical and biochemical pregnancy parameters of the study group (n = 41) and the control group (n = 66) per fresh embryo transfer procedures (n = 107) we found no significant differences. Freeze all cycles were excluded from the study. No significant differences concerning previous pregnancies and childbirth were detected. Limitations, reasons for caution: The study is a pilot study as the majority of the studies using α -chymotrypsin was conducted up to three decades ago, comparison of data must be interpreted in the light of the fact that since then, IVF has seen a rapid evolution of technology and culture techniques. Wider implications of the findings: The use of mild α -chymotrypsin treatment of semen samples in case of hyperviscosity does not appear to impact negatively on the fertilization rates after ART and could be regarded as an additional method to induce liquefaction of highly viscous semen samples in IVF... Trial registration number: not applicable